MUA Sebagai Tren Karir Anak Muda Dalam Mengurangi Pengangguran di Kecamatan Belik - Tutik, Tutik (Lembaga Riset Ilmiah, 2022)
MUA is one of the new types of businesses that is on the rise among young people because it is easy and does not require difficult conditions to follow. The large number of MUA business actors and the ease of young people to join have resulted in the emergence of slightly adverse competition, namely the price problem. The purpose of this study is to analyze the career trends of young people in the field of Bridal Make Up Artist. The method used is descriptive qualitative, namely analyzing the findings in the field. The result of this study is that the career trend of young people in the MUA type of business is very profitable because it can have an impact on decreasing the unemployment rate, besides that the MUA business can also bring up other types of businesses as support, including decoration services, entertainment, catering, photographers and Wedding Organizer services. With the positive impact given, it needs special attention from the local government to be developed.